Periodontitis relates to benign prostatic hyperplasia via the gut microbiota and fecal metabolome - Guo, Xing-Pei; Yang, Jun; Wu, Lan; Fang, Cheng; Gu, Jia-Min; Li, Fei; Liu, Han-Song; Li, Lu-Yao; Wang, Shuang-Ying (Frontiers in Microbiology, 2023)
Periodontitis is associated with benign prostatic hyperplasia (BPH)，whether it related to gut microbiota and metabonomics is unclear. We established ligature-induced periodontitis (EP), testosterone-induced BPH, and composite rat models. Fecal samples were collected to detect gut microbiota by 16S rDNA sequencing and metabonomics were detected by liquid chromatography tandem mass spectrometry (LC-MS/MS). Sequencing results revealed differential gut microbiota composition between EP+BPH group and other three groups. The abundances of Ruminococcus flavefaciens were significantly increased in EP+BPH group compared with other groups. Tenericutes, Mollicutes, RF39 and Ruminococcus gnavus were significantly decreased in EP+BPH group compared with BPH group, while Ruminococcus callidus and Escherichia were significantly decreased compared with EP group. For gut metabonomics, LC-MS/MS showed that fecal metabolites and seven metabolic pathways were changed in EP+BPH group, such as biosynthesis of unsaturated fatty acids, steroid hormone biosynthesis. Correlation analysis showed that the alterations of gut metabolism were significantly correlated with differential gut microbiota, such as Ruminococcus callidus and Ruminococcus flavefaciens. Our study highlights the relationship of periodontitis and BPH, the alterations of gut microbiota and metabolites may be involved in two diseases, which provides new idea for prevention and treatment of patients with periodontitis concurrent BPH.